Candlelight in Quintero = Luz de vela en Quintero - Petreman, David (Dos Madres, 2011)
“In poems often slender as Chile itself, David Petreman has paid tribute to the country in a luminous sequence in which nature has an elemental presence and the people he comes to know so well retain their compassion in challenging circumstances. That they also retain a sense of culture’s value is no small part of their experience, and this is what we may first pick up from reading Candlelight in Quintero. Replete with the scents and sights of the place, the poems still respond to the deeper challenge of showing the feelings and relationships that make up the real Chile.”